(±)‐Atrachinenins A—C, Three Pairs of Caged C27 Meroterpenoids from the Rhizomes of Atractylodes chinensis. Issue 4 (23rd December 2021) - Chen, Fei‐Long; Liu, Dong‐Li; Fu, Jing; Yang, Ji; Bai, Li‐Ping; Zhang, Wei; Jiang, Zhi‐Hong; Zhu, Guo‐Yuan
Abstract : Comprehensive Summary (±)‐Atrachinenins A—C (1—3), three meroterpenoids possessing novel C27 skeletons, were isolated from the rhizomes of Atractylodes chinensis . (±)‐Atrachinenin A (1) possesses an unprecedented cage‐like skeleton with a fused 6/6/5/5 tetracyclic system (decahy‐dro‐1, 5:4a, 7‐dimethanobenzo[7]annulene), which may be formed by the intermolecular cyclization of (±)‐atrachinenin C (3). Compared to 1, (±)‐atrachinenin B (2) features an additional unique five‐membered peroxyl bridge ring to form a complex 6/6/5/5/5 cyclic ring system. Their structures and absolute configurations were elucidated by HRESIMS, NMR spectroscopic data, ECD calculation, and X‐ray diffraction. A plausible biogenetic pathway was proposed. Compound 1 exhibited potential TGF‐ β inhibitory activity at 25 μmol/L. Abstract : (±)‐Atrachinenins A—C (1 —3 ), novel C27 meroterpenoids possessing the 6/6/5/5, 6/6/5/5/5, and 6/6/5 ring system, respectively, were isolated from Atractylodes Chinensis . Compound 1 exhibited potential TGF‐ β inhibitory activity at 25 μmol/L.